Income, distance and spatial effects in the Monocentric model. The Barcelona Metropolitan Area case. - Rafa Madariaga; Joan Carles Martori; Ramon Oller (European Regional Science Association (ERSA), 2011)
This paper focuses on the income distribution of households in Barcelona Metropolitan Area. For this purpose we use the Monocentric model. As the basic model does not have direct implications for this distribution, we survey the extensions of the model that have been used in empirical literature. One of the most promising ways is to introduce externalities in the decision process; they can result directly from exogenous amenities (natural traits of urban area) or be created directly by other agents' decisions. In this case, a spatial lag model and spatial error model are suited for the empirical purposes. We present evidence that any model with spatial effects improves significantly the econometric results.
Keywords: 330